Genomic Insights into the Colistin Resistant mcr-Carrying Escherichia coli Strains in a Tertiary Hospital in China - Guoli Li; Xinyang Li; Yuye Wu; Juan Xu; Fang He (MDPI AG, 2022)
Colistin is an important antimicrobial agent in the treatment of infections caused by multidrug resistant (MDR) Gram-negative bacteria. The horizontal transfer of mobile colistin resistance gene (mcr) poses a major threat to the public health worldwide. In this study, a total of thirteen mcr-carrying Escherichia coli (MCREC) strains were recovered from a tertiary hospital in Zhejiang, China, between 2016 and 2019. The minimum inhibitory concentration (MIC) of antimicrobial agents, epidemiological characteristics, and transmission dynamics of mcr-carrying isolates were analyzed using antimicrobial susceptibility testing, whole-genome sequencing, S1 nuclease pulsed-field gel electrophoresis (S1-PFGE), and southern blotting analysis. All strains were discovered to be resistant to colistin, and the majority displayed MDR phenotype. However, none of the 13 MCREC strains were resistant to carbapenems. The 13 MCREC isolates were divided into 10 different STs, including ST744, ST156, ST453, ST410, ST57, ST131, ST7034, ST2599, ST457, and ST13239, in which ST13239 was discovered for the first time. Based on core genome single nucleotide polymorphism (cgSNP) analysis, no clear epidemiological link was discovered in these strains with the exception of EC2118 and EC3807, which differ by just one SNP. A total of 35 antimicrobial resistance genes which can be divided into 14 classes were identified from the 13 MCREC isolates. According to S1-PFGE and southern blotting analyses, all 13 MCREC strains had plasmid-mediated mcr-1, and nine of them carried conjugative plasmids. In conclusion, our study revealed the emergence and dissemination of colistin-resistant E. coli isolates carrying mcr-1 in a Chinese hospital, which poses a potential risk to anti-infective therapy. More efforts should be taken to monitor the prevalence of mcr-1-carrying bacteria in China.